Determination of the Hydrogenase Status of Individual Legume Nodules by a Methylene Blue Reduction Assay - Lambert, Grant R. (1985)
We adapted a method for the rapid screening of colonies of free-living Rhizobium japonicum for hydrogenase activity to determine the hydrogenase status of individual soybean nodules. Crude bacteroid suspensions from nodules containing strains known to be hydrogen uptake positive (Hup(+)) caused a localized decolorization of filter paper disks, whereas suspensions from nodules arising from inoculation with hydrogen uptake-negative (Hup(−)) mutants or strains did not decolorize the disks. The reliability of the method was demonstrated by its successful application to 29 slow-growing rhizobia. The Hup phenotype on methylene blue filters agreed with that determined amperometrically with either methylene blue or oxygen as the electron acceptor.